AI and Islamic Communication: Technological Innovations for Dakwah Broadcasting in the Digital Era - Priyatna, Surya; Nuwairah, Nahed (Da’wa and Communication Faculty of the Sunan Ampel State Islamic University, Surabaya, Indonesia., 2024)
The advent of Artificial Intelligence (AI) has ushered in transformative changes across various sectors, including religious communication and broadcasting. This paper explores the integration of AI within the realm of Islamic communication, specifically focusing on technological innovations that enhance the effectiveness and reach of dakwah (Islamic preaching) in the digital era. By leveraging AI, Islamic communicators can automate content creation, analyze audience engagement, and personalize communication strategies, thereby making dakwah more relevant and impactful. The study delves into the theoretical foundations of AI in communication, presenting a comprehensive overview of how AI technologies can be harnessed to revolutionize dakwah practices. Through the implementation of natural language processing, machine learning, and data analytics, AI provides tools for crafting engaging and personalized Islamic messages that resonate with diverse audiences. Furthermore, the paper examines case studies where AI has successfully been integrated into dakwah initiatives, showcasing the practical benefits and challenges encountered. By adopting AI-driven approaches, Islamic broadcasters can achieve greater engagement, efficient content dissemination, and insightful audience analysis. This research underscores the potential of AI to not only modernize dakwah but also ensure its alignment with contemporary digital communication trends, ultimately contributing to the sustained propagation of Islamic teachings in the modern world.